2009
DOI: 10.1158/1078-0432.ccr-08-2865
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Splice Variants: Polymorphism, Risk, and Isoform-Specific Regulation in Prostate Cancer

Abstract: Purpose: Alternative CCND1 splicing results in cyclin D1b, which has specialized, protumorigenic functions in prostate not shared by the cyclin D1a (full length) isoform. Here, the frequency, tumor relevance, and mechanisms controlling cyclin D1b were challenged. Experimental Design: First, relative expression of both cyclin D1 isoforms was determined in prostate adenocarcinomas. Second, relevance of the androgen axis was determined. Third, minigenes were created to interrogate the role of the G/A870 polymorph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 68 publications
(110 reference statements)
2
110
1
Order By: Relevance
“…Consistent with the greater transforming potential of the constitutively nuclear D1a mutant, D1b transforms NIH-3T3 cells with much greater efficiency than does D1a (Solomon et al 2003). D1b has been shown to associate with the androgen receptor (AR), but, unlike D1a, D1b fails to inhibit AR transcriptional activity, a phenomenon of particular relevance to PCa, which shows frequent upregulation of cyclin D1b (Burd et al 2006;Comstock et al 2009). …”
Section: Cyclin D1mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the greater transforming potential of the constitutively nuclear D1a mutant, D1b transforms NIH-3T3 cells with much greater efficiency than does D1a (Solomon et al 2003). D1b has been shown to associate with the androgen receptor (AR), but, unlike D1a, D1b fails to inhibit AR transcriptional activity, a phenomenon of particular relevance to PCa, which shows frequent upregulation of cyclin D1b (Burd et al 2006;Comstock et al 2009). …”
Section: Cyclin D1mentioning
confidence: 99%
“…A common polymorphism that occurs near the 59 splice site of exon 4 influences the extent of cyclin D1b produced. The G870A polymorphism, with a reported allele frequency of 42% in one European population, has been associated with production of D1b (Betticher et al 1995;Comstock et al 2009). The polymorphism occurs at the very last nucleotide of exon 4 and may affect the recognition of exon 4 by the splicing machinery.…”
Section: Cyclin D1mentioning
confidence: 99%
“…In addition, it is well-known that the common variant rs9344 A allele modifies a splicing donor site and predisposes for an alternatively spliced transcript of the cyclin D1 protein (cyclin D1b). 28 In transcript b, no splicing occurs at the exon 4-intron 4 boundary, and exon 5 is missing. 1 Most variants found in 3¢UTRs of the patients are reported to be within conserved blocks, as are the majority of the variants in the promoter regions and the exons.…”
Section: Functional Analysismentioning
confidence: 99%
“…However, examination of 2Â2 tables reveals that LD between the CCND1-10/13/20 haplotype and rs9344 is nevertheless highly significant ( Table 6). Given that it has been demonstrated that this polymorphism is not independently predictive of cancer and that additional events may be necessary to induce cyclin D1b production, 28 we examined whether the presence of rare variants along the CCND1 gene is in any way associated with genotype at this position. We found that patients who carry at least one rare variant are more likely to also carry the rs9344 G allele than cases who do not harbor rare variants.…”
Section: Rs9344 G/a and Rare Variantsmentioning
confidence: 99%
“…Unfortunately, little is known concerning the mechanisms, pathways, and/or components of splicing in PCa. Overall Scope: Previously it been demonstrated that cyclin D1, a key modulator of androgen/AR-dependent transcription and proliferation, is alternatively spliced in PCa (5). Published data have suggested that SF2 and cyclin D1 isoforms have oncogenic functions (6,7) suggesting a potential link between splicing and proliferation.…”
Section: Introductionmentioning
confidence: 99%